Decarbonizing the Aligarh Muslim University Campus: An Experiential Analysis of Initiatives, their Impact and Lessons Learned - Mohammad Rihan; Tariq Mansoor (Universitas Diponegoro, 2022)
The climate crisis is the biggest existential threat to humanity in present times. Realizing this the United Nations have taken several important measures to address this challenge and prevent the rise in temperature of the earth. Increased concentration of carbon Dioxide in the environment is the major contributor to the global warming. Energy produced through the fossil fuels is a great factor behind this increase in CO2. The use of energy sources which do not produce CO2 are to be adopted and promoted aggressively.Universities have to play a crucial role in achieving this shared goal of humanity of saving the environment. The universities have to adopt sustainable development plans in their campuses, implement green energy sources and promote a culture of energy efficiency and conservation. In addition, the universities have to address the research questions in this area and train the manpower also. The Aligarh Muslim University, a leading university of India has been contributing towards these goals. This paper describes the initiatives of the university in adopting green sources of energy, energy efficiency and conservation. The future plans based on the experiential learning are also explained. Keyword: Green Energy, Energy Efficiency, Solar Energy, Energy Conservation, AMU